On a feature of temperature dependence of contact resistivity for ohmic contacts to n-Si with an n⁺ -n doping step - Sachenko, A.V.; Belyaev, A.E.; Boltovets, N.S.; Vinogradov, A.O.; Pilipenko, V.A.; Petlitskaya, T.V.; Anischik, V.M.; Konakova, R.V.; Korostinskaya, T.V.; Kostylyov, V.P.; Kudryk, Ya.Ya.; Lyapin, V.G.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
We present both theoretical and experimental temperature dependences of
contact resistivity ρс(Т) for ohmic contacts to the silicon n⁺
-n-structures whose n⁺
-layer
was formed using phosphorus diffusion or ion implantation. The ρс(Т) dependence was
measured in the 125–375 K temperature range with the transmission line method, with
allowance made for conduction in both the n⁺
-layer and n⁺
-n doping step.